Intrinsic and Extrinsic Analysis of Abid Husain Qureshi’s Art - Dr. Wardah Naeem Bukhari; Dr. Muhammad Asghar (Corresponding Author); Dr. Munazza Rashid; Mirza Mohsin Latif; Baneen Nazir (Al-Qanṭara, 2024)
Figurative art has historically been a trendy subject among Pakistani artists. Abid Husain Qureshi, on the other hand, has concentrated especially on human sorrow and loss from a variety of perspectives, which provides us with views into Pakistan's whole past and history. He has also researched human psychology and its intricacies. His paintings are enhanced by the way he arranges the materials to represent the subject matter best. To emphasize the meaning of the subject matter even more, he also used color. Therefore, the current paper's goal is to examine and thoroughly analyze all the artwork that Qureshi created during his life. This study's method is based on both intrinsic and extrinsic analysis. It will pay special attention to its aesthetics and underlying philosophical ideas, which have shaped his entire body of work.